2013
DOI: 10.1158/1538-7445.am2013-564
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 564: Foxo3a regulates cell cycle arrest through the regulation of p53, p21 and GADD45 signaling activity in Quercetin-treated MDA-MB-231 breast cancer cells.

Abstract: Forkhead box O (FoxO) transcription factors play an important role in multiple signaling pathways and physiological and pathological processes including apoptosis, proliferation metabolism, immunity, and tumorigenesis. Activation of the FoxO subfamily in cells can upregulate cell-cycle inhibitors p21Cip1 and p27Kip1 and downregulate the cell-cycle regulator cyclin D1/2, consequently leading to G1/S arrest of cells. Recently, quercetin has attracted much attention in relation to its anticancer ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Previous studies have reported that DNA damage and other environmental stresses may induce the GADD45-like gene expression either through TP53 or by other means [ 7 – 9 ]. Once GADD45 proteins are induced, they participate in cell cycle arrest [ 10 ], DNA repair [ 11 ] or apoptosis [ 12 ]. All three GADD45 family members directly activate MTK1/MEKK4 kinases in response to environmental stresses, resulting in apoptosis induction through the JNK and P38 pathways [ 13 ], while GADD45β can also inhibit the JNK kinase MKK7 to suppress the JNK pathway signaling [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that DNA damage and other environmental stresses may induce the GADD45-like gene expression either through TP53 or by other means [ 7 – 9 ]. Once GADD45 proteins are induced, they participate in cell cycle arrest [ 10 ], DNA repair [ 11 ] or apoptosis [ 12 ]. All three GADD45 family members directly activate MTK1/MEKK4 kinases in response to environmental stresses, resulting in apoptosis induction through the JNK and P38 pathways [ 13 ], while GADD45β can also inhibit the JNK kinase MKK7 to suppress the JNK pathway signaling [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Forkhead box class O1 (Foxo1) is one of the earliest members identified in the Foxo family, and is also the most representative of the Foxo family. Previous studies had demonstrated that they serve an important role in a number of physiological and pathological processes, including proliferation, apoptosis, phagocytosis, metabolism, inflammation, differentiation and oxidative stress (13,14). Previous studies revealed that Foxo1 mediates dendritic cells and macrophages in order to regulate associated target genes in inflammatory responses (15); osteoclasts, dendritic cells and macrophages share a common precursor cell line.…”
Section: Hif-1-mediated Expression Of Foxo1 Serves An Important Role mentioning
confidence: 99%